Importance of a second spasm provocation test: Four cases with an initial negative spasm provocation test - Teragawa, Hiroki (World J Cardiol, 2017)
The spasm provocation test (SPT) is an important test in the diagnosis of vasospastic angina (VSA). In many cases, this test is performed as the gold standard test, and VSA is considered not present if the SPT is negative. However, some patients continue to experience chest symptoms despite a negative SPT. In this study, we report four cases in which SPT was repeated to evaluate chest symptoms despite the negative results of the first SPT. Two men in their 70s, one woman in her 60s, and one woman in her 70s, all with chest symptoms, underwent a second SPT at 4, 3, 2, and 3 years, respectively, after the first SPT, which was negative. Three patients had positive results in the second SPT (75%). In conclusion, even when SPT is negative, the diagnosis of VSA should be made with clinical symptoms in consideration. In some cases, a second SPT may be required to confirm the diagnosis of VSA.